Kontribusi Leverage, Likuiditas dan Ukuran Perusahaan Terhadap Profitabilitas dalam Industri Food And Beverage di BEI Tahun 2019-2023 - Lalita Zabrina Buchori; Ida Ayu Sri Brahmayanti (Jurnal Bisnis Kreatif dan Inovatif, 2025)
This study aims to analyze the effect of leverage, liquidity, and company size on profitability in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Testing was conducted both partially and simultaneously to obtain a comprehensive picture of the relationship between variables. This study uses a quantitative approach with a sample of 14 companies selected through a purposive sampling method based on certain criteria, such as the completeness of annual financial reports during the study period and the availability of relevant data. The data used are secondary data obtained from the official IDX website (www.idx.co.id), including annual financial reports containing information on total assets, total liabilities, total equity, financial ratios, and the company's profit level. Data analysis was carried out using the multiple linear regression method using SPSS version 26 software, so that the effect of each independent variable on the dependent variable can be tested both individually and together. The results of the study indicate that simultaneously, the variables leverage (X1), liquidity (X2), and company size (X3) have a significant effect on profitability (Y). However, partial test results revealed that leverage had a negative and significant effect on profitability, indicating that a high proportion of debt can reduce a company's ability to generate profits. Meanwhile, liquidity and company size were not shown to have a significant influence on profitability, suggesting that these factors are not the main determinants of profit performance in this sector. This study implies that food and beverage company management needs to carefully consider capital structure to maintain profitability. For further research, it is recommended to add other variables such as operational efficiency, sales growth, and dividend policy, as well as extend the observation period for more in-depth and representative analysis results.